RANCANG BANGUN APLIKASI KENDARAAN MOBIL OPERASIONAL BERBASIS MOBILE MENGGUNAKAN METODE WATERFALL PADA PT PELABUHAN INDONESIA (PERSERO) - Wardhani, Diky; Prialam , Abdi (Universitas Siber Indonesia, 2025)
The operational vehicle car booking application process is identified as an activity carried out by the operational support section of HR services. In this study, several problems were found, including the use of paper documents in the ordering process, manual collection of documents, and collection of fuel and E-Toll proof after ordering which still uses paper. This condition causes difficulties in maintaining the integrity of documentation, especially if paper documents are damaged or lost. The main objective of this research is to develop an information system that can increase effectiveness in supporting operational vehicle car booking activities and improve the accuracy and reliability of documentation. This operational vehicle car booking system will be developed using the Flutter programming language for mobile applications and MySQL as a database. The information system development used is the waterfall method. In addition, testing of operational vehicle car booking information systems uses the blackbox testing method. After all stages of the research were completed, positive test results were obtained which showed that all the functionality tested in the operational vehicle car booking application successfully met the expected results. Therefore, this application can be declared to function properly according to the needs with the specifications given.